MODIFIKASI MODUL SEQUENCE FLASHING LIGHT (SQFL) PADA BAR KE-21 DI BANDARA INTERNASIONAL HANG NADIM BATAM - Hutabarat, Gerald Christ Mario; Muhammad Caesar Akbar (Jurnal Penelitian, 2024)
On the Job Training activities at Batam International Airport there are things that are of concern, one of which is damage to one of the components in the Sequence Flashing Light (SQFL) module. What is meant by Sequence Flashing Light is a light that flashes sequentially in a clear color which is installed in the middle of the outermost approach light bar towards the Threshold. The problem lies in the 21st Runway 04 bar. Factors that cause the damage include bad weather conditions. Uncertainty can result in easy damage to electronic components due to being outdoors with an unstable environmental temperature. The problem affects the pilot's visibility during bad weather or at night when landing. Based on this background, the author intends to raise a report with the title "Modification of the Sequence Flashing Light (SQFL) Module at the 21st Bar at Hang Nadim International Airport, Batam."